Real impact of liver cirrhosis on the development of hepatocellular carcinoma in various liver diseases—meta‐analytic assessment - Kazuo Tarao; Akito Nozaki; Takaaki Ikeda; Akira Sato; Hirokazu Komatsu; Tatsuji Komatsu; Masataka Taguri; Katsuaki Tanaka (Cancer Medicine)
Abstract Background It is well known that the incidence of developing hepatocelluler carcinoma (HCC) is increased in liver cirrhosis of different etiologies. However, comparison of HCC incidence in various liver diseases has not yet been estimated. We surveyed this comparison. Methods The PubMed database was examined (1989‐2017) for studies published in English language regarding the prospective follow‐up results for the development of HCC in various liver diseases. A meta‐analysis was performed for each liver disease. Results The annual incidence (%) of HCC in the non‐cirrhotic stage and cirrhotic stage, and the ratio of HCC incidence in the cirrhotic stage/non‐cirrhotic stage were as follows. (a) hepatitis B virus liver disease: 0.37%→3.23% (8.73‐fold), (b) hepatitis C virus liver diseases: 0.68%→4.81% (7.07‐fold), (c) primary biliary cholangitis (0.26%→1.79%, 6.88‐fold), (d) autoimmune hepatitis (0.19%→0.53%, 2.79‐fold), and (e) NASH (0.03%→1.35%, 45.00‐fold). Regarding primary hemochromatosis and alcoholic liver diseases, only follow‐up studies in the cirrhotic stage were presented, 1.20% and 2.06%, respectively. Conclusions When the liver diseases advance to cirrhosis, the incidence of HCC is markedly increased. The development of HCC must be closely monitored by ultrasonography, magnetic resonance imaging, and computed tomography, irrespective of the different kinds of liver diseases.